Effects of solamargine in hepatic metastasis of colorectal cancer: induction of ferroptosis and elimination of cancer stem cells - Shenglan Liu; Junhong Wu; Hao Huang; Bin Hu; Dong Xie; Fuqiang Cao; Jingxuan Li; Caiyao Guo; WeiJie Peng; Yanli Jin; Wei Dai (Chinese Medicine)
Abstract Background Colorectal cancer (CRC) is a prevalent malignant tumor globally, ranking third in incidence and second in mortality. Metastasis is the main cause of death in patients with CRC. Solanum nigrum L. (SNL), a traditional Chinese medicinal herb endowed with detoxification, blood circulation enhancement, and anti-swelling properties, has been widely used in folk prescriptions for cancer treatment in China. Solamargine (SM) is the major steroidal alkaloid glycoside purified from SNL. However, its role and mechanism against metastatic CRC are not yet clear. The purpose of this study was to evaluate the inhibitory effect of SM on human hepatic metastatic CRC and investigate its underlying mechanism. Methods CCK-8 assay, colony-formation assay, transwell assay, flow cytometry, tumoursphere formation assay, reverse-transcription quantitative PCR (RT-qPCR), Western blotting, transcriptomic sequencing and ferroptosis analysis were performed to reveal the efficacy and the underlying mechanism of SM in CRC cell lines. In vivo, allograft model, patient-derived xenograft (PDX) model, and liver metastatic model were performed to verify the effect of SM on the growth and metastasis of CRC. Results SM was found to suppress hepatic metastasis in CRC by effectively targeting key cellular processes, including proliferation, survival, and stemness. RNA sequencing showed that SM could induce ferroptosis, which was confirmed by elevated lipid reactive oxygen species (ROS) and downregulated glutathione peroxidase 4 (GPX4) and glutathione synthetase (GSS) in CRC cells and xenografts. Induction of ferroptosis by SM was regulated by nuclear factor erythroid 2-related factor 2 (Nrf2). Furthermore, downregulation of β-catenin was found to be fundamental for the SM-enabled cancer stem cells (CSCs) elimination and metastasis blockage in CRC. Conclusion Our results indicated that SM is a promising therapeutic drug to inhibit hepatic metastasis in CRC by inducing ferroptosis and impeding CSCs.